The Quest for an Alzheimer Therapy - Cappa, Stefano F. (Frontiers in Neurology, 2018)
This mini-review considers three different approaches to the therapy and prevention of Alzheimer’s disease (AD): replacement therapy, disease modification, and multi-level interventions. Each of these research frameworks has direct implications at the clinical level, leading to an emphasis on different timepoints of the AD continuum. While all perspectives continue to play an important role in current efforts to reach the ambitious target of of an effective therapy or prevention of AD by 2025, it is clear than novel paradigms are needed, including new models of clinical trial design. This goal can only be accomplished by a concerted effort of academia, governmental agencies and industry.